Toxicological evaluation of chronic administration of Catharanthus roseus extract in the adult albino rats - Elshama, Said Said; Osman, Hosam-Eldin Hussein; El-Kenawy, Ayman El-Meghawry (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
Herbal drugs are common use in many developing countries because of its effectiveness and low cost. World Health Organization approved its use as treatment for many diseases. So it should study efficacy and safety the natural source of these drugs. Catharanthus roseus is a popular ornamental plant. It contains about seventy alkaloids and used for multiple therapeutic purposes. Available literature on Cathranthus indicated to controversial issue about its safety. This study evaluates toxicological effect the leaf extract of Catharantus roseus in the rats by assessment biochemical and histopathological changes of liver and kidney, morphological changes of pancreas and heart with study some hematological parameters. Sixty albino rats were divided into three groups, each group consists of twenty rats. Control group received water, while second and third group received 300 and 400mg/kg of leaf extract of Catharanthus roseus, respectively and daily by orogastric tube for three months. Prolonged use of Catharanthus roseus led to significant abnormalities of liver and renal function tests, and some hematological parameters associated with hepatic, renal, cardiac and pancreatic histopathological changes which increased based on the dose. Repeated use of Catharanthus roseus caused hepatic, renal, hematological, cardiac and pancreatic toxicity depending on the dose.